Early Childhood Learning Media Design Using Macromedia Flash 8 - Cholil Bisri; Fahreza Shiddiq Siregar; Khairul Abdi; Putra Wan; Rafli Khalis Nugraha; Ali Ikhwan (LPPM Universitas Dharma Andalas, 2023)
In this day and age where technology is a necessity in everyday life for humans, technology is also used in the distribution of learning media for early childhood which is certainly very helpful in developments in the world of education. There are many learning media that can be used, such as multimedia, which is part of technological developments. By making it a learning medium, it is certain that early childhood can enjoy learning in a fun way. This research and design of instructional media aims to increase early childhood learning motivation by utilizing Macromedia Flash 8 technology. As we know, children prefer entertainment and games that make them more comfortable in learning. By making children's learning media by utilizing this technology, it is hoped that it can increase early childhood interest in learning so that later it will enable early childhood to be more creative and innovative. The use of this technological media can have a positive impact on early childhood in terms of carrying out learning. This study uses the waterfall method, where this method has stages such as design procedures, needs analysis, specifications and design, implementation and verification and the last is the validation stage.